Compressional residual stress in Bastogne boudins revealed by synchrotron X‐ray microdiffraction - Kai Chen; Martin Kunz; Yao Li; Eloisa Zepeda‐Alarcon; Manuel Sintubin; Hans‐Rudolf Wenk (Geophysical Research Letters)
Abstract Lattice distortions in crystals can be mapped at the micron scale using synchrotron X‐ray Laue microdiffraction (μXRD). From lattice distortions the shape and orientation of the elastic strain tensor can be derived and interpreted in terms of residual stress. Here we apply the new method to vein quartz from the original boudinage locality at Bastogne, Belgium. A long‐standing debate surrounds the kinematics of the Bastogne boudins. The μXRD measurements reveal a shortening residual elastic strain, perpendicular to the vein wall, corroborating the model that the Bastogne boudins formed by layer‐parallel shortening and not by layer‐parallel extension, as is in the geological community generally inferred by the process of boudinage.